THE RELATIONSHIP BETWEEN SIDE EFFECTS OF TUBERCULOSIS DRUG USE AND SGOT/SGPT VALUE OF INTENSIVE PHASE PATIENTS - Farroh Bintang Sabiti; Nur Anna Chalimah Sa’dyah (Universitas Muhammadiyah Magelang, 2022)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium Tuberculosis which has a rod shape and is acid-resistant. The prolonged consumption of anti-tuberculosis drugs can cause serious side effects. Side effects from the consumption of anti-tuberculosis drugs, namely the risk of hepatotoxicity, which is marked by an increase in the SGOT / SGPT value. This study aimed to determine the relationship between the duration of use, dosage and side effects of anti-tuberculosis drugs in tuberculosis patients, which had an effect on the SGOT / SGPT value at RSI Sultan Agung Semarang. This research is an analytical observational study with a cross-sectional design. The sample was 96 patients, and data collection was carried out in January-November 2020 at RSI Semarang. The instrument used in this study was patient medic record data. This study uses the Chi-Square test. The Chi-Square test results in 0.000 (p <0.05) so that it could be stated that there was a relationship between the use and side effects on the SGOT / SGPT value.